PENENTUAN PARAMETER KUNCI KUALITAS AIR SUNGAI BEDADUNG KABUPATEN JEMBER MENGGUNAKAN WATER QUALITY INDEX (Key determination of water quality parameter in Bedadung River, Jember Regency using water quality index method) - Elida Novita; Satria Priambada Dwija Kusuma; Hendra Andiananta Pradana (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2021)
ABSTRACT Determinion function of key parameters of water quality representing many parameters can be used to determine the water quality status . The purpose of the study were to analyse water quality status using Water Quality Index from Ministry of Environment of Mongolia and to select key parameter of water quality with discriminant analysis at Bedadung River. This research used 25 parameters (physicochemical and microbiology) were taken from 5 water sampling location at the period of 2016 to 2019. Location of water quality sampling were in urban area i.e. Patrang, Sumbesari, and Kaliwates Sub-district. The results showed that the water quality status calculation of the Bedadung River in urban area segment was 0.70 - 2.00 in clean and lightly - moderately polluted category. The key parameters from discriminant analysis were TSS, cobalt, sulfide, and chlorine. The most polluted parameters were sulfide and chlorine. The source of chlorine and sulfide pollution in Bedadung River were solid waste domestic exposure. Recommendation to reduce the level of contamination caused by garbage is development of small dam to facilitate the cleaning of garbage on the current season drought and education of the public to not throw garbage or waste in the Bedadung River. Key words: watershed; water quality index; discriminant analysis; Jember Regency ABSTRAKPenentuan parameter kunci dari kualitas air suatu badan air berfungsi untuk mewakili beberapa parameter kualitas air guna menentukan status kualitas airnya. Tujuan dari penulisan artikel ini yaitu untuk menganalisis status kualitas air menggunakan Indeks Kualitas Air dari Kementerian Lingkungan Hidup Mongolia dan memilih parameter kunci kualitas air dengan analisis diskriminan di Sungai Bedadung. Data yang digunakan pada kajian ini berupa parameter fisika-kimia dan mikrobiologi dari perairan Sungai Bedadung. Penelitian ini menggunakan 25 parameter yang diambil dari 5 lokasi pengambilan contoh air pada periode tahun 2016 - 2019. Lokasi pengambilan sampel kualitas air berada di segmen perkotaan yaitu Kecamatan Patrang, Sumbersari, dan Kaliwates. Hasil perhitungan status kualitas air Sungai Bedadung segmen perkotaan menunjukkan nilai 0,70 - 2,00 dalam kategori bersih dan tercemar ringan hingga sedang. Parameter utama dari analisis diskriminan yaitu TSS, kobalt, sulfida, dan klorin. Parameter yang paling tercemar yaitu sulfida dan klorin. Sumber pencemaran klorin dan sulfida di Sungai Bedadung adalah paparan limbah padat domestik. Rekomendasi yang diberikan untuk mengurangi tingkat pencemaran yang disebabkan oleh sampah yaitu membangun bendungan kecil untuk memudahkan pembersihan sampah pada musim kemarau yang sedang berlangsung serta mengedukasi masyarakat untuk tidak membuang sampah di Sungai Bedadung.Kata kunci: Daerah Aliran Sungai; indeks kualitas air; analisis diskriminan; Kabupaten Jember